2015
DOI: 10.1039/c4tc02373k
|View full text |Cite
|
Sign up to set email alerts
|

Isobenzofulvene-fullerene mono-adducts for organic photovoltaic applications

Abstract: IC60MA derivatives with up-shifted LUMO were synthesized and their OPV devices showed higherVocthan the corresponding PC60BM based device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(18 reference statements)
2
4
0
Order By: Relevance
“…Tseng et al synthesized three IC 60 MA derivatives namely: IC 60 MA-2C, IC 60 MA-3C and IC 60 MA-4C (Figure 5) with higher LUMO level than PC 61 BM and tested them in PTB7-based devices. As expected, the devices of PTB7 with ICMA derivatives all exhibited higher V oc than the reference device of PTB7:PC 61 BM [100]. However, the best PCE was still obtained with the reference PTB7:PC 61 BM devices (6.8%), while the devices with IC 60 MA-2C, IC 60 MA-3C and IC 60 MA-4C displayed PCEs of 6.0%, 5.1% and 6.5%, respectively.…”
Section: Devices Based On Ptb7supporting
confidence: 55%
“…Tseng et al synthesized three IC 60 MA derivatives namely: IC 60 MA-2C, IC 60 MA-3C and IC 60 MA-4C (Figure 5) with higher LUMO level than PC 61 BM and tested them in PTB7-based devices. As expected, the devices of PTB7 with ICMA derivatives all exhibited higher V oc than the reference device of PTB7:PC 61 BM [100]. However, the best PCE was still obtained with the reference PTB7:PC 61 BM devices (6.8%), while the devices with IC 60 MA-2C, IC 60 MA-3C and IC 60 MA-4C displayed PCEs of 6.0%, 5.1% and 6.5%, respectively.…”
Section: Devices Based On Ptb7supporting
confidence: 55%
“…All the J-V curves of devices with fulleropyrrolidine acceptors show some space charge limited current (SCLC) effects, and interestingly devices based on 70A display a characteristic S-shaped similar to S-shaped J-V curves that have been previously reported in fulleropyrrolidine-based OPVs [43]. We note that previous work has often reported novel fullerenes that despite displaying more favorable LUMO levels than PC 61 BM and PC 71 BM, gave rise to OPV devices with considerable lower PCE [34,46,47,[58][59][60][61][62][63][64] and also with simultaneously lower PCE and V OC [34,46,47,[62][63][64] than reference devices based on PC 61 BM and PC 71 BM. In the present work, among our fulleropyrrolidine-based devices the best efficiencies (η) are achieved by devices with the C 60 derivatives 60A (2.78%), 60B (2.20%), and 60C (2.04%).…”
Section: Resultssupporting
confidence: 67%
“…Together with the decrease of V OC and J SC for all devices (compared to the PC 71 BM) the fill-factor FF also decreases due to the mentioned J-V shape. At this point it is worth noting that a large number of previous studies in the literature have reported new fullerenes that despite exhibiting enhanced LUMO levels with respect to PC 61 BM or PC 71 BM, originated devices with considerably lower PCE [46][47][48][49][50][51][52][53][54][55] and also with simultaneously lower PCE and V OC [50][51][52][53][54][55] UV-Vis spectra of the blends and pure polymer, normalized based on the intensity of their 0-1 transition peak at~700 nm, are depicted in Figure 5. The polymer PffBT4T-2OD is the main responsible for the light absorption and the fullerenes contribute only a minor part to the total absorbance of the active layer in the visible region.…”
Section: Resultsmentioning
confidence: 99%